Optimum Currency Area in Asean 5 Countries: Is it Appropriate to Use American Dollar As the Standar Currency? - Feri Dwi Riyanto; Bunga Bunga Hidayati; Aji Purba Trapsila (Jurnal Ekonomi dan Studi Pembangunan, 2021)
Many times ASEAN countries experienced economic crisis in 1997/1998 and financial crisis in 2008. The similar patterns of cisis among those countries make some researchers conduct research of single currency unification. This research has a purpose to analyze the impact of ASEAN 5’s currencies (Rupiah, Ringgit, Singapore Dollar, Baht, and Peso) to a currency shock in the other ASEAN countries. The concept of this study uses the exchange rate approach pegged of ASEAN countries with American Dollars and Singapore Dollars. Furthermore, this research analyzes a symmetrical currency response to the currency shock in the other countries. The method of the study comes closer short-term and long-term models of Vector Auto regression (VAR) by using monthly data in real exchange rate variables from 1990 to 2019. The result of impulse response function (IRF) shows that responses to ASEAN currency pegged the currency to Singapore Dollars rather than US Dollars